Analisis Kemampuan Membaca Permulaan Pada Peserta Didik Kelas I Sekolah Dasar : Perspektif Kognitif dan Psikomotorik - Natasya Rey Fadila; Chandra Chandra; Salmaini Safitri Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Early reading is an important foundation in mastering language skills, especially for first grade elementary school students. Problems that often arise at this stage include difficulty in recognizing letters, arranging letters into words, and pronunciation and understanding simple reading. This study aims to analyze the early reading skills of first grade students in terms of cognitive and psychomotor aspects, and to identify factors that hinder their achievement. This study uses a descriptive quantitative approach with test instruments to assess cognitive abilities and observations to assess psychomotor skills. The subjects of the study consisted of five first grade students. The results showed that most students had very good cognitive abilities in early reading, but their psychomotor abilities tended to be low. A gap was found between theoretical understanding and practical skills of students. This finding emphasizes the importance of a balanced and holistic learning strategy so that students not only understand conceptually, but are also able to apply reading skills in real life.